The Effects of Classroom Anger, Strain, and Negative Emotions on Delinquency among Vocational School Students in China. Issue 2 (1st February 2022) - Zhang, Jinwu; Liu, Jianhong; Cui, Shan; Shuai, Honglan
ABSTRACT: General Strain Theory delineates the intervening paths from strain to deviance and crime, mediated by negative emotions. In addition to explaining individual strain-delinquency relationships, a macro version of General Strain Theory describes the effects of aggregate variables on individual delinquency and individual strain-delinquency associations. Using a sample of 902 students (Individual Level) nested in 30 classrooms (Classroom Level), the present study tests the macro version of General Strain Theory using Chinese data. The results revealed the differences among classrooms for their delinquency and provided evidence that classroom anger had an influence on individual delinquency. Classroom anger also reinforced the individual strain-delinquency and negative affect-delinquency associations. Limitations and future studies were discussed.